Knowledge, attitudes, and practices toward COVID-19: A cross-sectional study during normal management of the epidemic in China - Yang, Juan; Liao, Yuting; Hua, Qianhui; Sun, Chang; Lv, Huakun (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic is striking the world with serious public health and economic losses. Complying with precautionary measures is affected by knowledge, attitudes, and practices (KAP) toward COVID-19 among the general public, so it is urgent to know the public's awareness of COVID-19 as to promote the epidemic management of COVID-19 in China. Methods An online sample of Chinese residents was recruited. We administered a self-developed online KAP survey comprising 39 questions regarding awareness of COVID-19, transmission mode, symptoms, preventive measures, and respondents' attitudes and practices with respect to COVID-19. The total score of each item (knowledge, attitudes, and practices) adopts the ten points system, score of KAP is 30 points. Descriptive statistics, analysis of variance, and binomial logistic regression were used in the statistical analysis. Results Among respondents, average scores for COVID-19-related knowledge, attitudes, and practice were 8.94 ± 0.79, 5.97 ± 1.58, and 7.03 ± 3.14, respectively. 91.2% were aware that COVID-19 is an acute viral infection and 99.95% knew that wearing a mask is one way to prevent COVID-19 infection. Participants correctly identified the symptoms of COVID-19 with a high accuracy rate of over 85%. Conclusion Many adults in the present study had adequate knowledge, a positive attitude and engaged in correct practices against COVID-19. People in China have a high awareness of epidemic prevention and control. However, conducting KAP surveys among people with different demographic characteristics at different stages of the epidemic is important to improve public health education and implement proper COVID-19 prevention and control measures.